2015
DOI: 10.5539/ies.v8n13p27
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of Secondary Students towards the Use of GeoGebra in Learning Loci in Two Dimensions

Abstract: The use of computer software has good chance to form an efficient and powerful learning among the students. On the other hand, using open source software to teach mathematics in the school system of Malaysia, particularly in secondary school is still an uncertain issue. As a result, in an attempt to bring in a freeware, GeoGebra, this paper studies the attitude of form two students towards the utilization of GeoGebra in learning Loci in Two Dimensions. This study was conducted with 30 form two students from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The overall results demonstrate an enhancement in pupils' geometric thinking of second grade (Year 2) after the intervention which concurs with the findings of previous studies conducted in Malaysia (Rajagopal, et al 2015;Tay, 2003;Meng and Idris, 2012). The students who took the pretest have studied the 3-D and 2-D shapes in a conventional setting.…”
Section: Research Question 7 Is There a Significant Different In Visusupporting
confidence: 81%
“…The overall results demonstrate an enhancement in pupils' geometric thinking of second grade (Year 2) after the intervention which concurs with the findings of previous studies conducted in Malaysia (Rajagopal, et al 2015;Tay, 2003;Meng and Idris, 2012). The students who took the pretest have studied the 3-D and 2-D shapes in a conventional setting.…”
Section: Research Question 7 Is There a Significant Different In Visusupporting
confidence: 81%
“…ATU was the third most essential factor. Reference [31] and [32] have indicated that PU and PEOU significantly influence students' ATU of GeoGebra. Therefore, improving PU and PEOU can enhance ATU and usage intention.…”
Section: Discussionmentioning
confidence: 99%
“…PU PU, defined as -the degree to which a person believes that using a particular system would enhance his or her job performance‖ [54] (p. 320), is hypothesized to be a fundamental determinant of technology adoption. The results of [31] and [32] revealed that PU exerted a considerable influence on students' attitudes toward usage of GeoGebra. This study analyzed the effect of PU on behavioral intention and proposed the following hypothesis.…”
Section: Research Model and Hypothesesmentioning
confidence: 95%
See 1 more Smart Citation
“…A number of studies dealt with influence that ICT usage in Mathematics instruction can have on students' creativity, knowledge building, quality of knowledge and their academic achievements. Some of them suggest that ICT usage in the Mathematics instruction can boost students' parameters (Arbain & Shukor, 2015;Brown, 2010;Hopper, 2009;Rajagopal et al, 2015), but there are more studies (Bennett & Maton, 2010;Bullen et al, 2011;Oblinger & Oblinger, 2005;White & Le Cornu, 2011) showing that the context is the key factor in understanding quality and efficiency of ICT impact on students' parameters.…”
Section: Introductionmentioning
confidence: 99%